The incidence of cardiovascular events is largely reduced in patients with maximally tolerated drug therapy and lipoprotein apheresis. A single-center experience. (May 2015) - Sampietro, T.; Sbrana, F.; Bigazzi, F.; Ripoli, A.; Dal Pino, B.; Pasanisi, E.M.; Petersen, C.; Coceani, M.; Luciani, R.; Pianelli, M.
Abstract: Aim: Lipoprotein apheresis (LA) is the elective therapy for homozygous and other forms of familial hypercholesterolemia (FH) and familial combined hypercholesterolemia (FCH), resistant/intolerant to lipid lowering drugs, and hyperlipoproteinemia(a) for which drugs are not available. To assess the effect of LA on the incidence of adverse cardiac or vascular events (ACVE) at the time period of pre-initiation of apheresis and during the LA treatment. Methods: We collected data of 30 patients (mean age 62 ± 8 years, males 73%), with FH, or FCH and cardiovascular disease on maximally tolerated lipid lowering therapy and LA treatment (median 5 years, interquartile range 3–8 years). Associated hyperlipoproteinemia(a) was present in 16/30 subjects. The LA treatment was performed biweekly as clinically indicated by dextran-sulfate or heparin-induced LDL precipitation apheresis. The ACVE incidence, before and after treatment, was evaluated by statistical analyses. Results: The ACVE incidence occurred before and after the LA treatment inception, were 86 and 15 events respectively. Notably, 6/15 of ACVE were secondary to stent restenosis and 7/15 follow-up events occurred during the first 5 years. The AVCE rates/year were 0.58 and 0.13 respectively ( p  < 0.001). Conclusions: Our data confirm long-term efficacy and positive impact of LA on morbidity in patients with FH and FCH and atherosclerotic disease at maximally tolerated lipid lowering therapy.